Evolutionary conservation of protein dynamics: insights from all-atom molecular dynamics simulations of `peptidase' domain of Spt16 - Gaur, Neeraj K.; Ghosh, Biplab; Goyal, Venuka Durani; Kulkarni, Kiran; Makde, Ravindra D. (Journal of Biomolecular Structure and Dynamics, 2023)
Protein function is encoded in its sequence, manifested in its three-dimensional structure, and facilitated by its dynamics. Studies have suggested that protein structures with higher sequence similarity could have more similar patterns of dynamics. However, such studies of protein dynamics within and across protein families typically rely on coarse-grained models, or approximate metrics like crystallographic B-factors. This study uses mu s scale molecular dynamics (MD) simulations to explore the conservation of dynamics among homologs of similar to 50 kDa N-terminal module of Spt16 (Spt16N). Spt16N from Saccharomyces cerevisiae (Sc-Spt16N) and three of its homologs with 30-40% sequence identities were available in the PDB. To make our data-set more comprehensive, the crystal structure of an additional homolog (62% sequence identity with Sc-Spt16N) was solved at 1.7 angstrom resolution. Cumulative MD simulations of 6 mu s were carried out on these Spt16N structures and on two additional protein structures with varying degrees of similarity to it. The simulations revealed that correlation in patterns of backbone fluctuations vary linearly with sequence identity. This trend could not be inferred using crystallographic B-factors. Further, normal mode analysis suggested a similar pattern of inter-domain (inter-lobe) motions not only among Spt16N homologs, but also in the M24 peptidase structure. On the other hand, MD simulation results highlighted conserved motions that were found unique for Spt16N protein, this along with electrostatics trends shed light on functional aspects of Spt16N. Communicated by Ramaswamy H. Sarma.
Keywords: Backbone fluctuations; FACT complex; histone binding; interdomain motion; M24 peptidase

Atomically dispersed Co-Cu dual active sites in carbon networks as an efficient oxygen electrocatalyst - Sinha, Nibedita; Das, Chandni; Pal, Santanu; Urkude, Rajashri R.; Ahmed, Tanbir; Ghosh, Biplab; Roy, Poulomi (Dalton Transactions, 2025)
Single-atom metal-based electrocatalysts offer extended advantages by maximizing the utilization of active sites but often suffer from complex synthesis processes and low-density metal loading. The present work showcases a strategic design for integrating highly dense cobalt-copper dual atoms dispersed on a nitrogen-rich porous carbon network (CoCu-NGC). The atomically dispersed CoCu-NGC outperforms the ORR and OER activities of their single metallic counterparts (Co-NGC or Cu-NGC) and conventional noble-metal based electrocatalysts (Pt/C and RuO2). Benefitting from the electronic modulation in the dual SAC system, the CoCu-NGC displayed outstanding bifunctional performance with low Delta E values of 0.69 V in freshwater and 0.78 V in seawater, highlighting it as a potential alternative to the costly state-of-art electrocatalysts.

Deciphering the intricate mechanisms behind the selective oxidation of methane to C1 and C2 oxygenates over FeAu/γ-Al2O3 catalysts - Prabu, Marimuthu; Manikandan, Marimuthu; Rengam, B. Sathya Sai; Ramakrishnan, Archana; Raja, Abhishekram; Urkude, Rajashri R.; Ghosh, Biplab; Varghese, Jithin John; Raja, Thirumalaiswamy (Chemical Engineering Journal, 2025)
In this work, we demonstrate an eco-benign synthesis protocol for preparing gold nanoparticles and the role of the strong interaction between gold nanoparticles and iron oxide in FeAu/gamma-Al2O3 catalysts that render it an anionic (Au delta-) character while tailoring them in a smaller size. The multifunctional FeAu/gamma-Al2O3 catalyst selectively produces ethanol (95 % selectivity, similar to 240 mu mol(-1) cat) at a mild temperature of 75 degrees C without the addition of co-reactants during liquid phase methane oxidation with molecular oxygen. Conversely, Au/gamma-Al2O3 and Fe/gamma-Al2O3 catalysts exhibited high selectivity for CH3OH and HCHO. A high dispersion accompanied by strong electronic interaction between the Au delta–FeOx, as corroborated by diverse techniques, enables methane activation across the interface and coupling on the gold nanoparticles, which are responsible for the markedly improved formation of ethanol. Furthermore, in situ DRIFTS studies and DFT investigations point to a reaction mechanism of coupling of CH2OH and CH3 intermediates as the most likely route for ethanol formation.
Keywords: Anionic gold catalysts; Au-FeOx synergism; C-H bond activation; Ethanol; Methane oxidation; Methanol

Hydrogel electrolyte-mediated in situ Zn-anode modification and the Ru-RuO2/NGr-coated cathode for high-performance solid-state rechargeable Zn-air batteries - Kharabe, Geeta Pandurang; Verma, Tushar; Barik, Sidharth; Urkude, Rajashri R.; Ayasha, Nadeema; Ghosh, Biplab; Krishnamurty, Sailaja; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2025)
This work aims to deal with the challenges associated with designing complementary bifunctional electrocatalysts and a separator/membrane that enables rechargeable zinc-air batteries (RZABs) with nearly solid-state operability. This solid-state RZAB was accomplished by integrating a bifunctional electrocatalyst based on Ru-RuO2 interface nanoparticles supported on nitrogen-doped (N-doped) graphene (Ru-RuO2/NGr) and a dual-doped poly(acrylic acid) hydrogel (d-PAA) electrolyte soaked in KOH with sodium stannate additive. The catalyst shows enhanced activity and stability toward the two oxygen reactions, i.e., oxygen reduction and evolution reactions (ORR and OER), with a very low potential difference (Delta E) of 0.64 V. The computational insights bring out the electronic factors contributing to the enhanced catalytic activity of Ru-RuO2/NGr based on the charge density difference (CDD) between the interfaces. The disadvantages of the existing solid-state RZABs, such as their limited lifespan brought on by passivation, dendritic growth, corrosion, and shape change, have also been taken into account. The introduction of the stannate additive to the electrolyte induced an in situ Zn-anode modification, which subsequently improved the interfacial stability of the ZABs and, hence, the battery life cycles. The experimental observations reveal that, during the charging process, the Sn nanoparticles enable the homogeneous Zn deposition on the surface of the anode. Thus, the in situ Zn-anode surface modification assisted in achieving a high-rate cycle capability, viz., the homemade catalyst-based system exhibited continuous charge-discharge cycles for 20 h at a current density of 2.0 mA cm-2, with each cycle lasting for 5 min.
Keywords: Bifunctional Electrocatalyst; Core-ShellStructure; DFT study; electrolyte additive; Hydrogel; solid-state rechargeable zinc-airbattery; X-ray absorption spectroscopy

Multifunctional NiO/Ti3+-TiO2 for concurrent water reduction and glycerol oxidation to value added products by sunlight driven photocatalysis - Rajendran, Sivaraj; Saju, Simi; Mani, Sunesh S.; Asoka, Anantha Krishnan; Saha, Arindam; Arun, Pushkaran S.; Ghosh, Biplab; Mathew, Thomas; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2025)
The present work describes the synthesis of bifunctional-mesoporous-self-doped Ti3+ containing NiO/TiO2 photocatalysts for concurrent utilization of e- and h+ to produce H2 and value-added products (VAPs), respectively, from aqueous glycerol. UV-vis diffuse reflectance results and band gap analysis revealed an improved light absorption due to integration of Ni2+ with Ti3+/TiO2. Various electrochemical, PL and TRPL spectral analyses demonstrate p-n heterojunction formation between NiO and Ti3+-TiO2, which enhances charge separation and helps in achieving improved activity. HRTEM analysis of NiO/Ti3+-TiO2 nanocomposites revealed that NiO is highly dispersed on TiO2 with interfacial heterojunctions between them. XPS results demonstrate the partial reduction of Ti4+ to Ti3+ and Ni-Ti synergetic interaction in NiO/TiO2 to form NiO/Ti3+-TiO2 nanocomposites. EXAFS studies show that the Ni-O bond distance is similar to that of NiTiO3 suggesting electronic integration of components of the photocatalyst by forming a Ni2+-O-Ti3+/Ti4+ lattice network. Ni2+/Ti3+-TiO2 nanocomposites as a bifunctional photocatalyst exhibited significantly enhanced activity in H2 production and conversion of glycerol to VAPs, namely, glycolaldehyde, 1,3-dihydroxyacetone, and formic acid; formation of these products highlights not only oxidation, but also C-C cleavage of glycerol. The NiO/Ti3+-TiO2 photocatalysts fabricated in thin film form displayed higher photocatalytic efficiency than their powder counterpart. Among NiO/Ti3+-TiO2 nanocomposites NiT-3 exhibits the highest H2 yield at 15.62 mmol h-1 g-1, which is 38 times higher than that of bare TiO2. The enhanced photocatalytic activity is ascribed to the high charge carrier density, the synergistic interaction between Ni2+ and Ti3+-TiO2, formation of a p-n heterojunction at the interface between NiO and Ti3+-TiO2 and effective utilization of charge carriers for redox reactions.

Multifunctional NiO/Ti3+–TiO2 for concurrent water reduction and glycerol oxidation to value added products by sunlight driven photocatalysis - Rajendran, Sivaraj; Saju, Simi; Mani, Sunesh S.; Asoka, Anantha Krishnan; Saha, Arindam; Arun, Pushkaran S.; Ghosh, Biplab; Mathew, Thomas; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2025)
The present work describes the synthesis of bifunctional-mesoporous-self-doped Ti3+ containing NiO/TiO2 photocatalysts for concurrent utilization of e− and h+ to produce H2 and value-added products (VAPs), respectively, from aqueous glycerol. UV-vis diffuse reflectance results and band gap analysis revealed an improved light absorption due to integration of Ni2+ with Ti3+/TiO2. Various electrochemical, PL and TRPL spectral analyses demonstrate p–n heterojunction formation between NiO and Ti3+–TiO2, which enhances charge separation and helps in achieving improved activity. HRTEM analysis of NiO/Ti3+–TiO2 nanocomposites revealed that NiO is highly dispersed on TiO2 with interfacial heterojunctions between them. XPS results demonstrate the partial reduction of Ti4+ to Ti3+ and Ni–Ti synergetic interaction in NiO/TiO2 to form NiO/Ti3+–TiO2 nanocomposites. EXAFS studies show that the Ni–O bond distance is similar to that of NiTiO3 suggesting electronic integration of components of the photocatalyst by forming a Ni2+–O–Ti3+/Ti4+ lattice network. Ni2+/Ti3+–TiO2 nanocomposites as a bifunctional photocatalyst exhibited significantly enhanced activity in H2 production and conversion of glycerol to VAPs, namely, glycolaldehyde, 1,3-dihydroxyacetone, and formic acid; formation of these products highlights not only oxidation, but also C–C cleavage of glycerol. The NiO/Ti3+–TiO2 photocatalysts fabricated in thin film form displayed higher photocatalytic efficiency than their powder counterpart. Among NiO/Ti3+–TiO2 nanocomposites NiT-3 exhibits the highest H2 yield at 15.62 mmol h−1 g−1, which is 38 times higher than that of bare TiO2. The enhanced photocatalytic activity is ascribed to the high charge carrier density, the synergistic interaction between Ni2+ and Ti3+–TiO2, formation of a p–n heterojunction at the interface between NiO and Ti3+–TiO2 and effective utilization of charge carriers for redox reactions.

Towards improved activity and stability in RWGS reaction: Dispersed copper in mesoporous alumina matrix as a strategy for enhanced performance - Saju, Simi; Rajendran, Sivaraj; Oztas, Ulviye; Ruiz, Sergio Carrasco; Reina, Tomas Ramirez; Ghosh, Biplab; Sree, Sreeprasanth Pulinthanathu; Meena, Raghavendra; Li, Guanna; Bobadilla, Luis F.; Vinod, Chathakudath P.; Mathew, Thomas; et al. (Chemical Engineering Journal, 2025)
The development of highly performing Cu-based catalysts with high dispersion of Cu species in nanocrystalline form on a suitable oxide support is significant in reverse water gas shift (RWGS) reaction. We report a simple and robust one-pot sol-gel synthesis of mesoporous Al10-xCuxOy (m gamma-Al10-xCux-SG) catalysts with Cu species in a highly dispersed nanocrystalline form in the gamma-Al2O3 matrix and its high catalytic performance in RWGS reaction. The lack of long range structural order of copper species in m gamma-Al10-xCux-SG catalysts evidenced from Cu-K edge extended X-ray absorption fine structure (EXAFS) studies illustrates the fine distribution of copper species in mesoporous gamma-Al2O3 lattice. Activity study revealed that m gamma-Al10-xCux-SG catalysts showed significantly high CO2 conversion to CO and excellent catalytic stability compared to gamma-Al10-xCux-I prepared by conventional impregnation method. Mesoporous Al9Cu1 (m gamma-Al9Cu1) displayed a CO2 conversion of 45 % at 500 degrees C, which is about 2.8 times higher activity than conventional gamma-Al9Cu1-I catalyst with almost same Cu loading as that of m gamma-Al9Cu1 catalyst. Stability study at 500 degrees C over a period of 50 h revealed that m gamma-Al10-xCux-SG catalysts at low Cu loading (m gamma-Al9.9Cu0.1) showed excellent catalytic stability. The strong copper-alumina interaction in m gamma-Al10-xCux-SG catalysts with enhanced number of active sites at the copper-alumina interface as evidenced from field emission scanning electron microscope (FESEM), high-resolution transmission electron microscope (HRTEM), H2-temperature programmed reduction (H2-TPR), X-ray photoelectron spectroscopy (XPS), electrochemical characterization, and Cu-K edge EXAFS analysis enhances the activity and stability of the catalyst. Density functional theory (DFT) studies and the Operando DRIFTS-MS analysis of RWGS over m gamma-Al9Cu1 catalyst revealed that the mechanism of RWGS reaction to CO formation on m gamma-Al10-xCux-SG catalysts is preceded through the formation of a hydroxycarbonyl (OCOH) intermediate. The present synthesis strategy provides an opportunity for producing Cu-based catalysts with further enhanced activity and stability in RWGS reaction by suitable modification of the catalyst.